1993
DOI: 10.1016/0165-2427(93)90067-e
|View full text |Cite
|
Sign up to set email alerts
|

Number and distribution of T lymphocytes in the small intestinal mucosa of calves inoculated with rotavirus

Abstract: An understanding of the immune response to rotavirus is needed to develop effective prophylaxis. There is evidence that cell-mediated responses may be involved and to extend these observations, rotavirus antigen and the three major T cell subsets, BoCD4+, BoCD8+, and BoWC1+ gamma/delta lymphocytes were immunostained in tissue sections from calves killed at 2, 4, 6, 8 and 10 days post inoculation and quantified by image analysis. It was established that in control calves, BoCD4+ lymphocytes were predominantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Despite a large number of studies on the role of T cells in mediating protection against rotavirus infection in adult mice with various gene knockouts (protection against disease cannot be assessed in the adult mice model) [14][15][16][17][18], limited data is available on T cell immune responses to rotavirus in humans [19,20] or other out-bred native hosts, i.e. calves and pigs [21][22][23]. However, because of the potentially important role for CD4+ and CD8+ T cells in rotavirus immunity, especially in heterotypic protection as suggested by studies of influenza virus infections [24], it is important to quantify and characterize antigen-specific CD4+ and CD8+ T cells in an animal model of rotavirus disease as well as in human clinical trials for the development of new rotavirus vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large number of studies on the role of T cells in mediating protection against rotavirus infection in adult mice with various gene knockouts (protection against disease cannot be assessed in the adult mice model) [14][15][16][17][18], limited data is available on T cell immune responses to rotavirus in humans [19,20] or other out-bred native hosts, i.e. calves and pigs [21][22][23]. However, because of the potentially important role for CD4+ and CD8+ T cells in rotavirus immunity, especially in heterotypic protection as suggested by studies of influenza virus infections [24], it is important to quantify and characterize antigen-specific CD4+ and CD8+ T cells in an animal model of rotavirus disease as well as in human clinical trials for the development of new rotavirus vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…IEL also accumulate during murine viral infection with reovirus [45], and intestinal T cell numbers are increased in rotavirus-infected calves [46]. RRV infection induces a rapid expansion of CD8αβ TCRαβ IEL in infant NOD mice (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The ␥␦ + T cells which exist mainly in iIEL composed of the first defense line protecting the body away from microorganisms infection (1-5% in peripheral blood, 10-30% in iIEL) (Scimmas et al, 1994;Zhi et al, 2004). Parsons found that CD8 + T cells and ␥␦ + T lymphocytes increased significantly when infected by RV (Parsons et al, 1993).…”
Section: Discussionmentioning
confidence: 97%